Sexual violence against female undergraduates in a nigerian tertiary institution (2014)
Background: Worldwide, violence against women is becoming an increasingly recognized pandemic issue necessitating eradication and elimination. It occurs in various forms with resultant physical, sexual or psychological consequences. However, there is still denial and paucity of literature about the magnitude and pattern of this problem in Nigeria. Objective: This study was designed to determine the patterns of sexual violence among female undergraduates including their perceptions and attitude. Methods: It was a descriptive cross-sectional questionnaire based study involving 388 female undergraduates of the University of Ibadan, Ibadan, Nigeria. Multistage sampling technique using their halls of residence was used to select participants. The results were analyzed using statistical package for SPSS software version 16.0. The p-value was set at 0.05. Results: The mean age of respondents was 20 years and 382 (98.5%) of them were single. Only 31.2% were sexually exposed and the average age of sexual debut was 18 years. Most (78, 64.1%) cases of the first sexual intercourse occurred voluntarily. Two hundred and sixty two (67.6%) respondents had experienced at least one form of sexual abuse in the past. The commonest coercive sexual behaviour experienced was unwanted touching (53.4%). The perpetrators were mostly casual friends (63.7%) and most reported these incidences to friends. The respondents demonstrated good knowledge but poor attitude about sexual abuse. Eighteen (10.7%) admitted to prior rape which was mainly perpetrated by strangers with half admitting it adversely affected their relationship with the opposite sex. Conclusion: Sexual violence occurs in this environment but mainly goes unreported. There is good knowledge about the issues of sexual violence but there is need for improved attitude and reporting by victims.